Liquorice Intoxication Can Lead to Cardiac Arrest!. (22nd September 2020) - Attou, Rachid; Redant, Sébastien; Honore, Patrick M.; Preseau, Thierry; Hantson, Philippe; De Bels, David
Abstract : A 45-year-old man was admitted to the Emergency Department with fatigue and muscular weakness. Soon after hospital admission, he developed "torsades de pointe" and was successfully resuscitated. The admission laboratory investigations had revealed a profound hypokalemia (1.65 mmol/L). The patient had a long-term use of alcohol-free "pastis" in an attempt to reduce his chronic ethanol consumption. As the beverage likely contained a significant amount of liquorice, the diagnosis of glycyrrhizin chronic intoxication was suspected. The diagnosis of liquorice-related pseudohyperaldosteronism was assessed by normal plasma aldosterone levels and low plasma renin activity. Intravenous and oral supplementation of potassium was required for 5 days, and the patient had an uneventful follow-up.